A novel method to measure rim deformation in UHMWPE acetabular liners. (September 2018) - Partridge, Susan; Buckley, Paige; de Boer, Greg; Williams, Sophie
Highlights: A method to evaluate rim deformation on UHMWPE acetabular liners is described. Rim deformation was evaluated quantitatively and qualitatively. Liners from hip simulator tests and retrieved liners were measured. The method showed good repeatability. Abstract: Fluoroscopy studies of total hip replacement (THR) have shown that the femoral head and acetabular cup can separate in vivo, causing edge loading on the rim of the cup. Pre-clinical testing of THR involves ISO standard motion and loading parameters that are representative of a standard walking gait. However, a requirement for more robust testing of THR has been identified and protocols for edge loading in hip simulators have been developed. This technical note describes a method to measure rim wear and deformation on ultra-high molecular weight polyethylene acetabular liners using 2D contacting profilometry and Matlab ® analysis. The method is demonstrated on liners that have been subjected to edge loading in hip simulator tests and that have been retrieved at revision surgery. A quantitative and qualitative evaluation of the rim deformation was performed with good repeatability using the method.